Non-coding regions of nuclear-DNA-encoded mitochondrial genes and intergenic sequences are targeted by autoantibodies in breast cancer - Obaidat, Deya; Giordo, Roberta; Kleinbrink, Erica L.; Banisad, Emilia; Grossman, Lawrence I.; Arshad, Rooshan; Stark, Azadeh; Maroun, Marie-Claire; Lipovich, Leonard; Fernandez-Madrid, Félix (Frontiers in Genetics, 2023)
Autoantibodies against mitochondrial-derived antigens play a key role in chronic tissue inflammation in autoimmune disorders and cancers. Here, we identify autoreactive nuclear genomic DNA (nDNA)-encoded mitochondrial gene products (GAPDH, PKM2, GSTP1, SPATA5, MFF, TSPOAP1, PHB2, COA4, and HAGH) recognized by breast cancer (BC) patients’ sera as nonself, supporting a direct relationship of mitochondrial autoimmunity to breast carcinogenesis. Autoreactivity of multiple nDNA-encoded mitochondrial gene products are mapped to protein-coding regions, 3’ untranslated regions (UTRs), as well as introns. In addition, autoantibodies in BC sera targeted intergenic sequences which may be a part of non-coding RNA (lncRNA) genes, including known lncRNA genes such as LINC02381, and others were close to the coding genes ERCC4, CXCL13, SOX3, PCDH1, EDDM3B and GRB2 genes. Increasing evidence indicates that lncRNAs play a key role in carcinogenesis. Consistent with this, our findings suggest that lncRNAs, as well as mRNAs of nDNA-encoded mitochondrial genes, may mechanistically contribute to BC progression. This work supports a new paradigm of breast carcinogenesis based on a globally dysfunctional genome with altered function of multiple mitochondrial and non-mitochondrial oncogenic pathways caused by the effects of autoreactivity-induced dysregulation of multiple genes and their products. This autoimmunity-based model of carcinogenesis will open novel avenues for BC treatment.